P-157 "Fast Track" a Qualitative Assessment for Endoscopy. (February 2017) - Williams, Emmanuelle; Stuart, August; Patel, Ankit; Moyer, Matthew; Tinsley, Andrew; Coates, Matthew; Bobb, Anne
Abstract : Background: Endoscopic visualization play a vital role when determining possible progression of disease in inflammatory bowel disease (IBD), affecting the medical and surgical management of the patient. Waiting times for endoscopy can be long, specifically in high volume referral centers. The aim of this study was to assess the value of instituting a "Fast Track" program that aids in expediting IBD patients for urgent endoscopy as clinically indicated. Methods: At an academic care center with high volume referrals, a single half-day per week in a single endoscopy unit was dedicated for IBD patients that were evaluated in our IBD clinic and deemed to need urgent endoscopic evaluation. Our study retrospectively analyzed data from "Fast Track" from a 6 month period from February to August 2016. In addition to demographics, waiting time defined as the time from when the order was placed to the date of the procedure was collected. Periprocedural data collected was type of procedure, form of sedation (conscious or general), endoscopic and microscopic findings, changes to medical or surgical management and any SIBDQ or Harvey Bradshaw Index scores collected at clinic visits within 1 month of endoscopy. Results: Over a 6 month period, 36 patients were referred from our IBD Center Clinic for 38 total procedures. Average age was 37 years. Based on the fraction of patients for whom SIBDQ and HBI scores were collected within 1 month of endoscopy (n = 10), Fast Track patients had significantly lower SIBDQ scores (39.4 ± 11.6 versus 48.2 ± 13.6 P = 0.042) and trended towards higher HBI scores (9.0 ± 3.9 versus 7.1 ± 5.0 P = 0.20) compared with our overall IBD clinic population (n = 580) The average wait time was calculated at 18.6 days. We observed 0 no-shows or cancelled appointments for these procedures, compared with an expected 1.8 no shows and 2.5 cancellations based on our usual clinic rates. Of the 38 procedures, 18 (47.3%) were flexible sigmoidoscopies, 16 (42.1%) colonoscopies, 3 (7.9%) ileoscopies, and 1 (2.6%) combined ileoscopy and flexible sigmoidoscopy. 34/38 cases (89.5%) were with conscious sedation and 4/38 (10.5%) with general sedation. 27/38 procedures (71.0%) were done with biopsies and 22/27 (81.5%) biopsies showed active inflammation. In terms of post procedural clinical management, 6 of the procedures have not had follow up yet at the time of this abstract submission. Of the remaining 32 procedures, 26 (81.3%) cases did have a change in medical or surgical management and 6 (18.8%) did not. Conclusions: Important findings include a 0% no show rate and an average wait time of only 18.6 days. Of the procedures where biopsies were taken, 81.5% showed active disease. Of the cases that received follow up, 81.3% had a change in their medical management. Our study shows that a dedicated routine for urgent IBD patients resulted in a 100% show rate. Also, our study demonstrates earlier findings of active disease and ability for a change in clinical management.